The description of inmates’ coping skills of class IIA women's prison in Semarang - Elfi Rimayati; Sri Sayekti; Sri Redjeki (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2021)
Purpose - The purpose of this study was to determine the coping skills of inmates in living their lives. Method - The method used in this research was descriptive quantitative, with a population of 378 people consisting of 48 adult prisoners, 330 adult inmates. Sampling was based on the Krecjie table with a sample total of 182 people.Result - The results of calculating the coping skills of the inmates from the five indicators that have been determined obatained an average number of 76.7%. Based on the results of the average coping skills, it can be concluded that the coping skills of Class II A Women's Prison in Semarang are included in the good category.Implications – The results of this study are expected to be input in improving correctional services at the Class IIA Women's Prison in Semarang.Originality - This research is the study analysis coping skills of inmates in living their lives in the Class IIA Women's Prison in Semarang.***Tujuan - Tujuan dari penelitian ini adalah untuk mengetahui keterampilan koping narapidana dalam menjalani kehidupan mereka.Metode - Metode yang digunakan dalam penelitian ini adalah deskriptif kuantitatif, dengan populasi 378 orang yang terdiri dari 48 tahanan dewasa, 330 narapidana dewasa. Pengambilan sampel didasarkan pada tabel Krecjie dengan total sampel 182 orang.Hasil - Hasil penghitungan keterampilan koping narapidana dari lima indikator yang telah ditentukan ditampati jumlah rata-rata 76,7%. Berdasarkan hasil rata-rata keterampilan koping, dapat disimpulkan bahwa keterampilan koping dari kelas II penjara perempuan di Semarang termasuk dalam kategori baik.Implikasi - Hasil penelitian ini diharapkan menjadi input dalam meningkatkan layanan pemasyarakatan di penjara perempuan IIA kelas di SemarangOriginalitas - Penelitian ini adalah penelitian studi keterampilan mengatasi narapidana dalam menjalani kehidupan mereka di penjara wanita IIA di Semarang.